It takes three to tango in employment: Matching vocational education organisations, students and companies in labour markets - Mika Maliranta; Satu Nurmi; Hanna Virtanen (The Research Institute of the Finnish Economy (ETLA), 2007)
We examine the determinants of labour market status after the initial vocational basic education (ISCED 3) by use of unique linked register data on students, their parents, teachers, educational organisations and business companies in Finland. We distinguish between four outcomes: 1) employment 2) further studies 3) non-employment and 4) drop-out. The explanatory factors are classified into three main groups: the characteristics of 1) the educational organisation and their institutions, 2) the students and 3) the local business conditions. Teaching expenditures do not matter but teachers' skills do. Parental background plays a central role. Local business development matters for boys.
Keywords: H52; I21; J23; J24; 330; Education production; vocational education; employability; further studies; egional development; drop-out; Berufsausbildung; Berufsvorbereitung; Regionaler Arbeitsmarkt; Humankapital; Beschäftigungsfähigkeit; Finnland